Competitive advantage : creating and sustaining superior performance - Porter, Michael E. (Free P. New YorkUS, 1985)
Provides an activity-based view of the firm. Describes the types of competitive advantage and shows how a firm can achieve them. Identifies the value chain as the basic tool for diagnosing and finding ways to enhance competitive advantage. Addresses competitive scope both within an industry, and in related industries. Develops overall implications for offensive and defensive competitive strategy and includes ways of coping with uncertainty.